Membumikan Islam Melalui Sikap Keberagamaan - Ahdiah, M.Pd (AL-IBNOR, 2023)
Diversity clearly rests on one's understanding of one's religion. Religion is not only a set of rituals but also moral and social. In Islam the natural potential of man to be religious becomes part of the component of the human nature is created. Human beings have intellectual potential (intelligence) which is the basis of creative thinking and the potential for social life (the instinct of sociality), as well as the potential for good and bad lusts that are moving. Islam has never separated between spiritual (religious), temporal (peace), religious (related to religion), and profane (which is related to the world. Therefore, as a form of devotion of a Muslim to his religion he has an obligation to obey Allah Swt. and Prophet Muhammad Saw. as his messenger, as well as behave in accordance with the teachings of Islam to achieve world peace and the Hereafter for its adherents. The method used by researchers is the library research method. The literature method that researchers carry out is reading, recording and processing materials. Data collection instruments in literature are books and documents related to researchers' studies on the concept of grounding Islam through diversity. One way to ground Islam through religious attitudes is to establish good relations with fellow human beings through commendable attitudes as taught by Islamic teachings. A Muslim who dares to behave according to religious orders will slowly cultivate harmonious relations between religious people. So that the purpose of Islam as a religion that saves its adherents both in the world and in the hereafter will be realized.